A restoration ecology perspective on the treatment of inflammatory bowel disease. Issue 1 (10th December 2019) - Orr, Matthew R; Kocurek, Kathryn M; Bakos, Yong J; McDowell, Ryder C
Abstract: The human gut can be considered an ecosystem comprised of a community of microbes and nonliving components such as food metabolites and food additives. Chronic diseases are increasingly associated with disruption of this ecosystem. The science of restoration ecology was developed to restore degraded ecosystems, but its principles have not been applied widely to gut medicine, including the treatment of inflammatory bowel disease (IBD). One principle of ecological restoration is that 'passive' restoration, which involves removing an ecosystem disturbance, should occur before attempting additional 'active' interventions. We discuss evidence that poor diet is principle source of disturbance in IBD, and therefore requires better attention in its research and clinical care. Another restoration principle is that higher biodiversity may improve ecosystem behavior, but this idea has not been tested for its possible importance in donor stool during fecal microbiota transplants. Lay summary: In patients with chronic disease the gut microbiome behaves like a disturbed ecosystem. Principles borrowed from the science of restoration ecology identify a need to better understand the influence of diet on treatment of inflammatory bowel disease and the importance of donor diversity in fecal microbiota transplants.